THE EFFECT OF THE AMOUNT OF BASIC AMINO ACIDS CONTAINED IN THE SILK LIQUID SYNTHESIZED IN THE SILK GLAND OF THE MULBERRY SILKWORM ON THE PROPERTIES OF SILK FIBER - Bekkamov Ch.I.; Turg‘unboeva N. A.; Allanazarova G.A.; To‘raeva Sh.D.; Ixlosov A.J. (European Journal of Interdisciplinary Research and Development, 2023)
It is known that the production of silk from the important physiological and biochemical processes in the body of the mulberry silkworm and its synthesis and release is an extremely important stage of the process of protein metabolism in mulberry silkworms. In this case, by the time the silkworm is 5 years old, after the silkworm is fully formed, it spends a lot of protein and a lot of energy in the silkworm's body to produce silk fibers. In order to create hygrothermic conditions as a protective shell for the umbilical period, the larva performs the task of secreting a special silk fluid in the cocoon, relying on the biological indicators of the silk gland.